Professional Competencies for Safety Representatives in China - Jansz, Janis; Jian, Le; Fan, Y. (Coal Enginnering Journal Office, 2010)
This paper addresses professional competencies required to develop healthy, safe and decent workplaces through the use of Safety Representatives. It compares the legal requirements in Western Australia and in China for workplaces to have Occupational Safety Representatives, the role of Safety Representatives, the competencies that are required to meet the legal duties of Safety Representatives and the legally required education for Safety Representatives to gain these competencies. The presentation concludes by outlining the benefits to the workplace, the industry and the country of Safety Representatives having the desired competencies.